1993
DOI: 10.1007/bf01983206
|View full text |Cite
|
Sign up to set email alerts
|

The clinical performance of the Multiload IUD. II. The influence of age

Abstract: Six thousand four hundred and sixty-two Multiload IUDs were inserted (3606 MLCu375 and 2856 MLCu250). In this study, we determined the acceptance and safety of Multiload IUD use in different age groups. Results were analyzed according to the usual life table method. The pregnancy rate was higher with the users of MLCu250 than with the MLCu375 in a clear relation to age group. Expulsion and bleeding and/or pain rates were higher with younger women in both IUD types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The volume of menstrual flow (less than normal or normal), dysmenorrhoea (no or yes), uterine position (anteverted, midposition, or retroverted), and parity (1 or ≥2), which were possible risk factors according to the literature, [8][9][10][11][12][13] were considered as potential confounding factors. In the first multivariate analysis, the above covariates were adjusted to estimate the adjusted odds ratio (aOR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of menstrual flow (less than normal or normal), dysmenorrhoea (no or yes), uterine position (anteverted, midposition, or retroverted), and parity (1 or ≥2), which were possible risk factors according to the literature, [8][9][10][11][12][13] were considered as potential confounding factors. In the first multivariate analysis, the above covariates were adjusted to estimate the adjusted odds ratio (aOR).…”
Section: Discussionmentioning
confidence: 99%
“…9 Young maternal age, heavy menstruation, dysmenorrhoea, uterine position, and the service provider's experience with regard to insertion were reported to be associated with expulsion or removal for displacement. [10][11][12][13][14][15] One hypothesis for IUD expulsion or displacement is dimensional incompatibility between the uterine cavity and the IUD. Castro found that the expulsion rate within 1 and 2 years of MLCu375 was more than four times higher for women with an endometrial cavity length of ≥45 mm, compared with those with a cavity length of <45 mm (P < 0.01) 16 ; however, two prospective studies failed to find any association between endometrial cavity length and the expulsion rate of IUDs.…”
Section: Introductionmentioning
confidence: 99%